Biosafety and potency of high-molecular-weight hyaluronic acid with intratympanic dexamethasone delivery for acute hearing loss - Hwang, Yu-Jung; Oh, Seung Ha; Lee, Jun Ho; Park, Moo Kyun; Suh, Myung-Whan (Frontiers in Pharmacology, 2024)
Objective: This study evaluated the potential of high-molecular-weight hyaluronic acid (HHA) as an intratympanic (IT) drug delivery vehicle for dexamethasone (D) in treating acute hearing loss. We compared the efficacy, safety, and residence time of HHA to the standard-of-care IT drug delivery method.Methods: Endoscopic examinations were used to track tympanic membrane (TM) healing post-IT injection. Micro-computed tomography (CT) was used to gauge drug/vehicle persistence in the bulla air space. Histological analyses covered the middle ear, TM, and hair cell counts. Auditory brainstem responses (ABR) were used to measure hearing thresholds, while high-performance liquid chromatography (HPLC) was employed to quantify cochlear perilymph dexamethasone concentrations.The HHA + D group had a notably prolonged drug/vehicle residence time in the bulla (41 ± 27 days) compared to the saline + D group (1.1 ± 0.3 days). Complete TM healing occurred without adverse effects. Histology revealed no significant intergroup differences or adverse outcomes. Hearing recovery trends favored the HHA + D group, with 85.0% of ears showing clinically meaningful improvement. D concentrations in cochlear perilymph were roughly double in the HHA group. Conclusion: HHA is a promising vehicle for IT drug delivery in treating acute hearing loss. It ensures extended residence time, augmented drug concentrations in targeted tissues, and safety. These results highlight the potential for HHA + D to excel beyond existing standard-of-care treatments for acute hearing loss.